Response of Rice Variety Nagina 22 (N22) and its Putative Mutants to Aluminium Toxicity Conditions in North-East India - Longkumer, Limasunep; Rai, Mayank; Tyagi, Wricha (International Journal of Bio-resource and Stress Management, 2022)
The study was performed to evaluate the wildtype genotype Nagina 22 (N22) and its mutants generated by ethyl methyl sulphonate (EMS)for aluminium (Al) toxicity tolerance. Based on performance under upland acidic field conditions on the basis of twelve different traits,among several available M4N22 mutants,four putative mutants N 714, N 721, N 4249 and N 4487 were selected for hydroponics evaluation. The seeds of the four selected lines were subjected to germination and grown in modified Magnacava’s broth supplemented with varying doses of AlCl3 under aseptic conditionsand phenotypic variations for traits like root length, shoot length, root biomass and shoot biomass were recorded. Haematoxylin staining of roots were also carried out on the seedlings grown under control as well as Al toxicity conditions which further revealed that putative mutants N 721 and N 4249 were better performers when compared to N22. Additionally, twelve candidate gene based markers targeting four known Al toxicity tolerance genes resulted in detection of gel based polymorphism for markers AR051-2, AR051-3 and OsFRLD4-1. These putative variations need further validation by running the markers on a set of at least 10 individual putative mutants and sequencing. Al toxicity tolerance in rice is a quantitative trait, these identified mutants can be used to obtain better understanding of tolerance mechanisms and then if possibleuse them synergistically to obtain better tolerance.